2021
DOI: 10.1038/s41598-021-83891-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sex differentiation-related microRNA and long non-coding RNA in Takifugu rubripes gonads

Abstract: Although sex determination and differentiation are key developmental processes in animals, the involvement of non-coding RNA in the regulation of this process is still not clarified. The tiger pufferfish (Takifugu rubripes) is one of the most economically important marine cultured species in Asia, but analyses of miRNA and long non-coding RNA (lncRNA) at early sex differentiation stages have not been conducted yet. In our study, high-throughput sequencing technology was used to sequence transcriptome libraries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 63 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…In addition, the regulatory role of lncRNAs mediated by miRNAs may also be involved in other biological processes, but the composition and molecular mechanism of the lncRNA-miRNA-mRNA axis need to be confirmed. For example, the differential expression of miRNAs and lncRNAs was also found in tiger pufferfish ( Takifugu rubripes , T. rubripes ) of different sexes ( 109 ). Compared with female gonads, 79 lncRNAs were upregulated and 51 were downregulated in male gonads, while 3 mature miRNAs were upregulated and 3 mature miRNAs were downregulated.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the regulatory role of lncRNAs mediated by miRNAs may also be involved in other biological processes, but the composition and molecular mechanism of the lncRNA-miRNA-mRNA axis need to be confirmed. For example, the differential expression of miRNAs and lncRNAs was also found in tiger pufferfish ( Takifugu rubripes , T. rubripes ) of different sexes ( 109 ). Compared with female gonads, 79 lncRNAs were upregulated and 51 were downregulated in male gonads, while 3 mature miRNAs were upregulated and 3 mature miRNAs were downregulated.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Compared with female gonads, 79 lncRNAs were upregulated and 51 were downregulated in male gonads, while 3 mature miRNAs were upregulated and 3 mature miRNAs were downregulated. Moreover, several lncRNAs and miRNAs were also predicted to regulate the expression of sex-related genes in T. rubripes gonads, such as lnc_000338, lnc_000690, lnc_000370, fru-miR-15b, novel-167, and novel-318 ( 109 ). In the central nervous system (CNS) of the weakly electric brown ghost knifefish ( Apteronotus leptorhynchus , A. leptorhynchus ), a broad variety of ncRNAs were identified, including lncRNAs, miRNAs, snRNAs, snoRNAs, and other ncRNA sequences ( 110 ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Epigenetic mechanisms are also responsible for governing gene-hormonal-environmental interactions. There is a considerable amount of data from teleost fish showing that miRNAs and lncRNAs are involved in sex determination processes and gonadal differentiation (Bizuayehu et al 2012; Juanchich et al 2013; Jing et al 2014; Lau et al 2014; Xiao et al 2014; Juanchich et al 2016; Tao et al 2016; Wang et al 2017; Pinhal et al 2018; Qiu et al 2018; Yan et al 2021). Studies have also brought up the potential roles of ncRNAs in the regulation of immune responses in teleost fish (Wang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found that lncRNAs primarily work by interacting with miRNAs and interfering with gene expression [40][41][42][43][44]. Functional analysis indicated that HOXA-AS3 participated in regulating various cell biological processes via numerous mechanisms, including cell proliferation, apoptosis, invasion, metastasis, chemotherapy sensitivity, endothelium inflammation, and MSCslineage differentiation.…”
Section: The Regulatory Mechanisms Of Hoxa-as3 In Human Diseases and ...mentioning
confidence: 99%